Security engineering: Phisical security measures for high-risk personnel - Cice, Jelena S.; Andrejić, Marko D.; Dragović, Nebojša K. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The design of physical security measures is a specialized technical area that does not fall in the normal skill record and resume of commanders, architects, engineers, and project managers. This document provides guidance to those parties tasked with implementing existing and emerging physical protection system requirements: -    Creation of a single-source reference for the design and construction of physical security measures for high-risk personnel (HRP). -    Promulgation of multi-service standard recommendations and considerations. -    Potential increase of productivity of HRP and reduced temporary housing costs through clarification of considerations, guidance on planning, and provision of design solutions. -    Reduction of facility project costs. -    Better performance of modernized facilities, in terms of force protection, than original facilities. Throughout this process you must ensure: confidentiality, appropriate Public Relations, sustainability, compliance with all industrial guidelines and legal and regulatory requirement, constant review and revision to accommodate new circumstances or threats. Introduction Physical security is an extremely broad topic. It encompasses access control devices such as smart cards, air filtration and fireproofing. It is also heavily reliant on infrastructure. This means that many of the ideal physical security measures may not be economically or physically feasible for existing sites. Many businesses do not have the option of building their own facility from the ground up; thus physical security often must be integrated into an existing structure. This limits the overall set of security measures that can be installed. There is an aspect of physical security that is often overlooked; the humans that interact with it. Humans commit crime for a number of reasons. The document focuses on two building types: the HRP office and the HRP residence. HRP are personnel who are likely to be terrorist or criminal targets based on their grade, assignment, symbolic value, criticality, and threat and vulnerability assessment. Levels of protection The recommendations contained in this criterion are intended to minimize the possibility of HRP casualties in buildings or portions of buildings in which they work and live. These recommendations provide appropriate and implementable measures to establish a level of protection against terrorist attacks where no known threat of terrorist activity currently exists. While complete protection against all potential threats is cost prohibitive, the intent of these recommendations can be achieved through prudent master planning, real estate acquisition, and design and construction practices. Tag number The tag number at the beginning of each physical security measure (recommendation) is unique and is intended to be a communication aid when linking the requirement (recommendation) to the supporting text or commentary. The three-character tag number uses the following legend. Tag Number First Character -The first character is an abbreviation for the defense zone layer that is most applicable for the countermeasure. “S” is used to represent site or external zone issues. “P” is used to represent the perimeter zone. “G” is used to represent issues relative to the property grounds. “E” is used to represent issues associated with the building exterior of the HRP office or residence. “I” is used to represent issues associated with the building interior. “H” is used to represent issues associated with the safe room or safe haven. Tag Number Second Character - The second character is a sequential number for countermeasures in a given zone - a requirement or a recommendation. This number ensures a unique tag number. Tag Number Third Character- The third character indicates whether the countermeasure is applicable to offices, residences, or both (common). “O” indicates a requirement or recommendation unique to offices. “R” represents a requirement or recommendation to residences. “C” represents a common requirement or recommendation applicable to offices and residences. Alternate and equivalent means or methods While listed physical security measures may be very specific, the intent is to achieve a certain level of protection for the HRP. If a requirement can be met by alternate and equivalent means or methods, then that variance should be accepted when proven to provide the equivalent level of protection. Common recommendations The recommendations in this section apply to both HRP offices and residences - S-1C: Final Approach Routes, S-2C: HRP Vehicle Parking, S-3C: Response Forces, S-4C: DoD Compound, P-1C: Subterranean Openings, E-1C: Number of Levels, E-2C: Window Locks, E-3C: Minimize Number of Exterior Doors, E-4C: Exterior Door Material, E-5C: Door Swing, E-6C: Exterior Door Hinges, E-7C: Exterior Door Jambs, I-1C: Skylights, I-2C: Furniture Layout, H-1C: Safe Room/Haven. Office recommendations In addition to the common recommendations for HRP buildings, the following additional physical protection measures are recommended for HRP offices - S-5O: Minimum Standards, I-3O: Internal Controlled Access Area, I-4O: Primary Access Door, I-5O: Other Access Doors, I-6O: HRP Office Door Frame Construction, I-7O: Office Construction, I-8O: CCTV. Residence recommendations In addition to the common recommendations for both HRP buildings, additional physical protection measures are recommended for HRP residences. Many of the recommendations are based on the assumption that the HRP residence is not located on a military installation- S-6R: Neighborhood, S-7R: Building Appearance, S-8R: Commute Route, S-9R: Emergency Services, S-10R: Crime Area, S-11R: Vehicular Approaches, P-2R: Perimeter Boundary, P-3R: Egress Route Viewing, P-4R: Vehicle Access Points, P-5R: Perimeter CCTV, P-6R: Perimeter IDS, G-1R: Standoff Distance, G-2R: Vantage Points, G-3R: HRP POV Parking, G-4R: Security Lighting: Provide security lighting around the residential exterior, G-5R: Unobstructed Space, G-6R: Access Control Point, G-7R: Visitor Parking, E-8R: Exterior Door Locks, E-9R: Windows, E-10R: Under-building Access Control, E-11R: Roof Access, E-12R: Residential Mailbox Guidelines, E-13R: Trash Receptacles, I-9R: Fire Protection System, I-10R: Intrusion Detection System (IDS).   Conclusion The challenge is twofold. The first challenge is to reach an agreement that something needs to be done. This involves altering mindsets, building consensus and getting senior management support. The second challenge is in developing and implementing an effective and tailor-made integrated physical security plan. This plan consists of three mutually supporting elements – physical security measures, operational procedures and policies. Physical security covers all the devices, technologies and specialist materials for perimeter, external and internal protection. This covers everything from sensors and closed-circuit television to barriers, lighting and access controls for HRP offices and residences. The following crucial elements must be taken into account – deterrence, detection, delay and response and then recovery and re-assessment. All are mitigation measures. These are the foundations on which any integrated physical security plan must be built.
Keywords: standards; high-risk personnel; protection; infrastructure; requirements; Physical security; Guidance; designing